EFFECTIVENESS OF POSTPARTUM EXERCISE FOR POSPARTUM WOMEN ON UTERINE INVOLUTION - Meirita Herawati Mei; Ary Oktora Sri Rahayu (Jurnal Smart Kebidanan, 2024)
Postpartum exercise plays an important role in the process of uterine involution. The involution process will proceed well if uterine contractions are strong, so action must be taken to improve uterine contractions. Efforts to control bleeding from the placenta by improving strong contractions and retraction of myometrial fibers with postpartum exercises. The aim of this research is to determine the effectiveness of postpartum exercises for postpartum mothers. on Uterine Involution at the Pujud Community Health Center, Rokan Hilir Regency. This type of research is a quasi-experimental design. The population in this study were postpartum mothers, who were taken using a purposive sampling technique. Of the 17 postpartum mothers in the Pujud Community Health Center Working Area, Rokan Hilir Regency, before postpartum exercise there was a decrease in Rapid TFU of 0 (0%), a decrease in Normal TFU of 8 (47.1), a decrease in Slow TFU of 9 (52.9) and after After postpartum exercise was carried out, there was a rapid decrease in TFU in 11 people (64.7%), there was a decrease in normal TFU in 6 (35.3), there was a slow decrease in TFU in 0 (0). There was a significant influence between postpartum exercise and uterine involution as seen from the height measurement. Uterine fundus with the One-Sample Test results above show that the P value is 0.000 < 0.05. So, in accordance with the basis for decision making in statistical tests, it can be concluded that postpartum exercise carried out before and after is effective in reducing the fundal height of the uterus (TFU) of postpartum mothers at the Pujud Community Health Center, Rokan Hilir Regency. It is hoped that all postpartum mothers can understand the benefits of postpartum exercise for uterine involution process. .